Zipping up tetraazaperylene: synthesis of tetraazacoronenes via double coupling in the bay positions - Eichelmann, Robert; Rippel, Daniel; Ballmann, Joachim; Gade, Lutz H. (Chemical communications, 2023)
Substituted tetraazacoronene fluorophores have been obtained selectively by double Suzuki-Miyaura cross coupling of symmetrically substituted 1,2-bis(pinacolatoboryl)alkenes with a bay-substituted octaazaperopyrenedioxide (OAPPDO). Subsequent Scholl reaction of the dimethoxyphenylated derivative allowed further π-extension of the azaperylene core, yielding a highly redox-active bis(phenanthro)tetraazacoronene.
Gesehen am 24.10.2023